2008
DOI: 10.1016/j.colsurfa.2007.03.045
|View full text |Cite
|
Sign up to set email alerts
|

How does a non-ionic hydrophobically modified telechelic polymer interact with a non-ionic vesicle? Rheological aspects

Abstract: The association between hydrophobically modified polyethylene glycol, HM-PEG, and non-ionic vesicles of tetraethylene glycol monododecyl ether, C 12 E 4 , was investigated. HM-PEG is in a triblock form, with an alkyl chain attached to each hydrophilic polymer-end. Such polymer structure is denoted as telechelic. The vesicle average radius was measured by self-diffusion measurements. The system exhibits both a monophasic gel and biphasic regions. The monophasic region was characterized from a rheological point … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…5, the zero-shear viscosity for the HMHEC-lipid mixture does not become lower than for the pure HMHEC solution. Previous studies for mixtures of telechelic HMPs and surfactant vesicles reported increasing viscosity and elastic properties with increasing surfactant concentration [23,24]. It is not known whether the solution viscosity will decrease when the surfactant concentration becomes high enough.…”
Section: Viscosity Behavior Of Hmhec-phospholipid Vesicles Solutionmentioning
confidence: 94%
See 2 more Smart Citations
“…5, the zero-shear viscosity for the HMHEC-lipid mixture does not become lower than for the pure HMHEC solution. Previous studies for mixtures of telechelic HMPs and surfactant vesicles reported increasing viscosity and elastic properties with increasing surfactant concentration [23,24]. It is not known whether the solution viscosity will decrease when the surfactant concentration becomes high enough.…”
Section: Viscosity Behavior Of Hmhec-phospholipid Vesicles Solutionmentioning
confidence: 94%
“…Formation of a gel network with a large elastic modulus independent of frequency was reported for hydrophobically modified chitosan in catanionic vesicles [21]. For telechelic HMP, Medronho et al examined hydrophobically modified polyethylene glycol (HMPEG) with catanionic vesicles [23], while Santos et al studied HMPEG with C 12 E 4 vesicles [24]. Both studies observed phase separation and enhanced viscoelasticity due to the bridging mechanism originating from hydrophobic attraction.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…There is less work done on the fundamental properties on vesicles compared to microemulsions with added HM polymers. Such hydrophobically modified polymers can interact with vesicles and interconnect them within vesicle solutions [144,145,146,147,148] (Figure 11A). However, the vesicle/polymer systems are more complicated because, unlike in the case of microemulsions and micelles, the structure of the vesicles do not necessarily remain intact upon the addition of hydrophobically modified polymers.…”
Section: Micellar Systems Microemulsions or Vesicles Cross-linkedmentioning
confidence: 99%
“…In any case, the addition of hydrophobically modified linear polymers to vesicle solutions leads to the formation of networks. These networks have higher elasticity with higher polymer concentration [144,145,146]. Here again, it is necessary that the hydrophilic part of the polymer is longer than the distance between vesicle membranes to form bridges.…”
Section: Micellar Systems Microemulsions or Vesicles Cross-linkedmentioning
confidence: 99%